Answer:
Step-by-step explanation:
We have by definition
[tex]Cov(X,Y) = E[(x – M_x)(Y – M_y)][/tex]
where Mx and My are means of X and Y respectively
a) [tex]E[(x – M_x)(Y – M_y)]\\= E(x,y) - E(x,My)-E(y,Mx)+M_x M_y\\=E(x,y) -E(x) M_y -E(y) M_x +M_x M_y\\=E(x,y)-M_x M_y-M_x M_y+M_x M_y\\=E(x,y)-M_x M_y[/tex]
b) Since right side inside expectation is commutative, we get cov(x,y) = cov (y,x)
c) [tex]cov (x,x) = E(x-M_x)(x-M_x) = E(x-M_x)^2\\= Var(X)[/tex]
d) [tex]Cov(X + Z,Y)=E(x+z-M_{x+z} )(Z-M_z)\\=E{(x-M_x)+(Y-M_y)}(Z-M_z)\\\\=E{(x-M_x)}(Z-M_z)+E{+(Y-M_y)}(Z-M_z)= cov (x,y)+cov (z,y)[/tex]
f) Var(x+y) = [tex]E{(x-M_x)+(Y-M_y)}^2[/tex]
Expanding inside we get
=[tex]Var(x)+var(y)+2 cov (x,y)[/tex]